A High-Density Integrated Genetic Linkage and Radiation Hybrid Map of the Laboratory Rat - Steen, Robert G.; Kwitek-Black, Anne E.; Glenn, Christopher; Gullings-Handley, Jo; Van Etten, William; Atkinson, O. Scott; Appel, Diane; Twigger, Simon; Muir, Melanie; Mull, Tim; Granados, Mary; Kissebah, Mushira; et al. (Genome Research, 1999)
The laboratory rat (Rattus norvegicus) is a key animal model for biomedical research. However, the genetic infrastructure required for connecting phenotype and genotype in the rat is currently incomplete. Here, we report the construction and integration of two genomic maps: a dense genetic linkage map of the rat and the first radiation hybrid (RH) map of the rat. The genetic map was constructed in two F2 intercrosses (SHRSP × BN and FHH × ACI), containing a total of 4736 simple sequence length polymorphism (SSLP) markers. Allele sizes for 4328 of the genetic markers were characterized in 48 of the most commonly used inbred strains. The RH map is a lod ≥ 3 framework map, including 983 SSLPs, thereby allowing integration with markers on various genetic maps and with markers mapped on the RH panel. Together, the maps provide an integrated reference to >3000 genes and ESTs and >8500 genetic markers (5211 of our SSLPs and >3500 SSLPs developed by other groups). [Bihoreau et al. (1997); James and Tanigami, RHdb (http://www.ebi.ac.uk/RHdb/index.html); Wilder (http://www.nih.gov/niams/scientific/ratgbase); Serikawa et al. (1992); RATMAP server (http://ratmap.gen.gu.se)] RH maps (v. 2.0) have been posted on our web sites at http://goliath.ifrc.mcw.edu/LGR/index.htmlor http://curatools.curagen.com/ratmap. Both web sites provide an RH mapping server where investigators can localize their own RH vectors relative to this map. The raw data have been deposited in the RHdb database. Taken together, these maps provide the basic tools for rat genomics. The RH map provides the means to rapidly localize genetic markers, genes, and ESTs within the rat genome. These maps provide the basic tools for rat genomics. They will facilitate studies of multifactorial disease and functional genomics, allow construction of physical maps, and provide a scaffold for both directed and large-scale sequencing efforts and comparative genomics in this important experimental organism.
10.1101/gr.9.6.AP1